THEORETICAL FUNDAMENTALS OF REGIONAL CAPACITY RESEARCH - Mulesa , E.V. (The actual problems of regional economy development, 2020)
The purpose of the study is to deepen and develop approaches to defining the essence of the region's capacity, highlighting its varieties, studying the relationship and interdependence between them and identifying the impact of these components on the efficiency of the territory as a separate administrative-territorial unit. In the course of the research the methods of monographic and theoretical generalization were used - to substantiate the concept of the region's capacity and its varieties; system and regression analysis - in identifying the main problems of regional development on the principles of self-sufficiency; inductions and deductions - to prove the similarity of the problems of regional development of territories in the context of local government reform, etc. The theoretical approaches of the concept of capacity studied in the work allowed to reveal it as a complex indicator, which includes a number of additional determinants (competitiveness, institutional, investment, organizational, tax and financial capacity), each of which is an integral part of successful community development. in today's conditions. The essential characteristics of each type of capacity are revealed, their interdependence and influence on the development of the region as an independent and self-sufficient administrative-territorial unit are determined. The main shortcomings in the interpretation of a concept taking into account the point of view of leading economists and as a result formed their own vision of their theoretical essence. The scientific novelty lies in the disclosure of fundamentally new criteria for the capacity of regions, taking into account existing practical experience and proving their direct impact on the development of territories in general. The practical significance of the obtained results is that the theoretical provisions brought to the level of practical application can serve as a contribution to ensuring the effective functioning and development of the regions, taking into account the basic principles of decentralization reform.